KZ KZ - Bloomstein, Rex (United Kingdom : Rex Entertainment, 2006)
Mauthausen is a picturesque town on the banks of the river Danube in Upper Austria. Two kilometers from its town centre is a place that attracts bikers, busloads of tourists, parties of schoolchildren, people from all over the world. Tour guides come to work here every day, while nearby the locals go about their daily lives. This is a place where thousands upon thousands of people from over 30 nations were tortured and murdered. This site is the former KZ, German short for concentration camp. How does it feel to be a tourist at a former concentration camp? How does it feel to work here as a guide, day in day out? How does it feel to live here as a local with the dark secrets of the past? And what of those who have chosen this town to be their new home? A film about facing the demons of the past.
Keywords: Documentary films